Importance of Garni Activities in the Sustainable Tourism: A Case Study of Hotels - Javeed Ahmad Ganai (International Journal of Engineering and Management Research, 2021)
This article provides a broad overview of sustainability in the hospitality and tourist business, as well as content information on sustainability that could be useful in hospitality and tourism education. The study focuses on the following question in particular: What role does sustainability education play in the hospitality and tourism industry? Themes in sustainability education are recognised in the accommodation, meetings and events, and food and beverage sectors, as well as implementations of sustainability principles in hospitality and tourism operations and perspectives on the future direction of sustainability education in this subject.